Quality of cow dung composting fertilizer with additional starter solution of cow rumen contents - Amirul Nurdiansyah; Arqowi Pribadi; Dedy Suprayogi; Abdillah Akmal Karami (Konversi, 2023)
RPH Kedurus produces livestock solid waste in the form of cow dung as much as 750 kg/day and the content of cow rumen is 2 tons/day. The livestock solid waste can be processed by turning it into compost using the takakura composting method. This study aims to determine the characteristics of the compost according to the specified parameters (temperature, pH, moisture content, organic c, nitrogen, phosphorus, potassium, and the C/N ratio) and to determine the dose of use of a good cow rumen content solution to produce compost according to the quality standard of SNI 19-7030-2004. In this study, the treatments used were P0 with a composition of 3 kg of cow dung and 1 kg of rice husks, P1 with a composition of P0 and 100 mL of starter solution of cow rumen contents, P2 with a composition of P0 and 200 mL of starter solution of cow rumen contents, and P3 with a composition of P0 and 300 mL of starter solution for bovine rumen contents. Overall, the characteristics produced by the four treatments met the quality standards, while the optimum dosage for the use of rumen contents was found in treatment P2 with the use of 200 mL of starter bovine rumen contents and produced a temperature of 29 °C, pH 7.4, water content 14.2%, C. -organic 67 %, nitrogen 4.26 %, phosphorus P2O5 0.37 %, potassium K2O 2.21 %, and C/N ratio 15.7. The compost fertilizer produced can be used as an alternative organic fertilizer to be developed.